Prevalence and association of chronic musculoskeletal pain on self-management, glycemic control and quality of life among Chinese type 2 diabetes patients in primary care - Sit, Regina Ws; Wang, Bo; Ng, Wing-Sze; Abdullah, Adina; Ismail, Irmi Zarina; Goh, Lay-Hoon; Wong, Samuel Ys (Elsevier, 2022)
Aims To examine the prevalence of chronic musculoskeletal (MSK) pain and its association with diabetes self-management, glycemic control and health-related quality of life (HRQoL) in patients with diabetes mellitus (DM) in primary care.